In praise of mystery - Limón, Ada (Norton Young Readers, an imprint of W.W. Norton & Company, 2024)
"From U.S. Poet Laureate Ada Limón and Caldecott Honoree Peter Sís: a transcendent picture book featuring the poem that will travel into space aboard NASA's Europa Clipper. As part of her tenure as US poet laureate, Ada Limón has written 'In Praise of Mystery,' which will be engraved on the Europa Clipper spacecraft that launches to Jupiter and its moons in October 2024. Published here as Limón's debut picture book, this luminous poem is illustrated by celebrated and internationally renowned artist Peter Sís. In Praise of Mystery celebrates humankind's endless curiosity, asks us what it means to explore beyond our known world, and shows how the unknown can reflect us back to ourselves."--